2012
DOI: 10.1227/neu.0b013e318235d640
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Major Extracranial Injury in Traumatic Brain Injury

Abstract: MEI is an important prognostic factor for mortality in TBI patients. However, the effect varies by population, which explains the controversy in the literature. The strength of the effect is smaller in patients with more severe brain injury and depends on time of inclusion in a study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Our data for killed victims after TBI are in accordance with others, who showed that non-cranial injury occurrence increased the risk of early mortality [40]. This increase in severe extra-cranial injuries might be explained either by a change in RTC victim recruitment (increased share of pedal cyclists and/or PTW users), or by modifications in procedures allowing a more sensitive diagnosis of TBI (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Our data for killed victims after TBI are in accordance with others, who showed that non-cranial injury occurrence increased the risk of early mortality [40]. This increase in severe extra-cranial injuries might be explained either by a change in RTC victim recruitment (increased share of pedal cyclists and/or PTW users), or by modifications in procedures allowing a more sensitive diagnosis of TBI (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…8 Also, in the TRIPOD statement, there is an item on the reporting of treatment received among participants of a study developing or validating a multivariable prediction model for diagnosis or prognosis. 9 In this article, we evaluate these different methods in situations that aim to develop a prognostic model generating predictions in case individuals were to remain untreated, which serve as input for treatment decisions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In fact, major extracranial injury has been reported as a prognostic factor for mortality in patients with TBI, but the strength of the effect is smaller in patients with more severe brain injury as is the most likely to occur in our series of patients who presented a high rate of isolated severe TBI from assault. 54,55 Besides the brain, the release of cell-free DNA from injured cells may occur peripherally, because DNA is present in the nucleus/ mitochondria of the majority of cell types and can be released into the circulation. Thus, extracerebral sources may contribute to the increase plasma DNA levels after multitrauma.…”
Section: Figmentioning
confidence: 99%